Decreased Plasma Levels of Angiotensin-Converting Enzyme Among Patients With Bipolar Disorder - Sanches, Marsal; Colpo, Gabriela D.; Cuellar, Valeria A.; Bockmann, Taya; Rogith, Deevakar; Soares, Jair C.; Teixeira, Antonio L. (Frontiers in Neuroscience, 2021)
Background: Dysfunctions in the renin-angiotensin system (RAS) seem to be involved in the pathophysiology of several mental illness, including schizophrenia and mood disorders. We carried out a cross-sectional study assessing the levels of RAS-related molecules among bipolar disorder (BD) patients compared to healthy controls. Methods: our sample consisted of 30 outpatients with BD type 1 (10 males, 20 females, age= 35.53 + 10.59 years, 14 euthymic, 16 experiencing mood episodes) and 30 healthy controls (10 males, 20 females, age= 34.83 + 11.49 years). Plasma levels of angiotensin-converting enzyme (ACE), angiotensin-converting enzyme 2 (ACE2), angiotensin-II (Ang II), and angiotensin (1-7) [Ang-(1–7)] were determined by ELISA. Results: BD patients experiencing ongoing mood episodes had significantly lower ACE levels compared to controls (median: 459.00 vs. 514.10, p< 0.05). There was no association between the levels of these biomarkers and clinical parameters. Conclusions: Our findings support the involvement of RAS dysfunction in the pathophysiology of BD. Considering the potential therapeutic implications linked to a better understanding of the role of RAS dysfunction in BD, studies allowing a better characterization of RAS-related molecules level and activity across different mood states are of high interest.